Microstructure and mechanical properties of CoCrFeMnNi high entropy alloy with ultrasonic nanocrystal surface modification process. (15th November 2020) - Listyawan, Timothy Alexander; Lee, Hyunjong; Park, Nokeun; Lee, Unhae
Abstract: In this study, mechanical properties improvement of equiatomic CoCrFeMnNi treated with an ultrasonic nanocrystal surface modification (UNSM) was studied. The applied UNSM treatment with static loads of 10 N, 20 N, and 60 N provided a severe plastic deformation, which produced a gradient structure. The near-surface area exhibited a high number of dislocation densities and deformation twin interaction, leading to a surface strengthening and hardness improvement of up to 112% than the deformation-free interior region. Increment of dislocation densities and deformation twin formation on the surface also enhanced the yield and ultimate tensile strength of the UNSM-treated specimens. Furthermore, the combination of hard nanocrystallites layer on the surface and ductile coarse grain in the specimen interior as a result of the UNSM treatment successfully maintained the strength–ductility balance of the CoCrFeMnNi.